High Frequency of Pathogenic Rearrangements in SPG11 and Extensive Contribution of Mutational Hotspots and Founder Alleles. Issue 7 (28th April 2016) - Günther, Sven; Elert‐Dobkowska, Ewelina; Soehn, Anne S.; Hinreiner, Sophie; Yoon, Grace; Heller, Raoul; Hellenbroich, Yorck; Hübner, Christian A.; Ray, Peter N.; Hehr, Ute; Bauer, Peter; Sulek, Anna; et al.
Abstract : Large deletions (red) and duplications (green) in the 40 exon SPG11 gene account for ∼19% of pathogenic alleles. Sequence level resolution shows that they may form at intronic Alu‐associated mutational hotspots (stippled lines) and/or represent recurrently identified ancient founder variants (*). ABSTRACT: Biallelic loss‐of‐function mutations in SPG11 cause a wide spectrum of recessively inherited, neurodegenerative disorders including hereditary spastic paraplegia (HSP), amyotrophic lateral sclerosis, and Charcot‐Marie‐Tooth disease. By comprehensive screening of three large cohorts of HSP index patients, we identified 83 alleles with "small" mutations and 13 alleles that carry large genomic rearrangements. Including relevant data from previous studies, we estimate that copy number variants (CNVs) account for ∼19% of pathogenic SPG11 alleles. The breakpoints for all novel and some previously reported CNVs were determined by long‐range PCR and sequencing. This revealed several Alu‐associated recombination hotspots. We also found evidence for additional mutational mechanisms, including for a two‐step event in which an Alu retrotransposition preceded the actual rearrangement. Apparently independent samples with identical breakpoints were analyzed by microsatellite PCRs. The resulting haplotypes suggested the existence of two rearrangement founder alleles. Our findings widen the spectra of mutations and mutational mechanisms in SPG11, underscore the pivotal role played by Alus, and are of high diagnostic relevance for a wide spectrum of clinical phenotypes including the most frequent form of recessive HSP.